Personal information retrieval for purposes of computer forensics - Dzikowski , Jakub (Studia Oeconomica Posnaniensia, 2013)
Committing a crime with the use of the Internet infrastructure is easier and involves less risk than committing a crime in the traditional way. Fighting crime in the cyberspace is possible due to footprints that each user leaves. This article discusses the problem of crime in the cyberspace, and issues related to combating such crime. A method is presented to search for the users’ personal information by extending available information about them. Additionally, empirical evaluation of the effectiveness of this method is performed.